VD_FINDINFO Décision / 2013 / 77 vom 13. November 2012 - VD Tribunal cantonal (2012)
CLASSEMENT DE LA PROCÉDURE, JUGE UNIQUE, FRAIS DE LA PROCÉDURE | 319 CPP (CH), 395 let. b CPP (CH), 426 al. 2 CPP (CH)